Sarcocornia obclavata (Amaranthaceae) a new species from Turkey - Yaprak, Ahmet Emre (Phytotaxa, 2012)
Sarcocornia obclavata is described as a new species from Mediterranean Turkey. The main morphological characters that separate S. obclavata from other Sarcocornia species are the obclavate shape of its fertile segments, which is more obvious at lower fertile segments. Sarcocornia obclavata differs from S. perennis in having cymes on fertile segments that clearly do not reach the upper edge. It differs from S. fruticosa in having curved hairs on the seed testa.